Interspecies communication in oral biofilm: An ocean of information. Issue 2 (May 2015) - Parashar, Amit; Parashar, Shashi; Zingade, Abhishek; Gupta, Shikha; Sanikop, Sheetal
Abstract The diversity of signalling opportunities within microbial communities, and the significant role of these molecules in coordinating gene expression and promoting biofilm formation, has provided the impetus to investigate the potential of inhibitory analogues to disrupt these networks, thereby providing mechanisms to control or influence the development of dental plaque. Within the oral biofilms, resident bacterial cells interact with one another and exchange messages in the form of signalling molecules and metabolites. In this review article, our aim is to elaborate the role of this quorum sensing and their involvement in pathogenesis to decipher information that can be useful to target pathways to control diseases.